The Influence of E-Trust, User’s Experiences, and Brand Equity on Gen Z Female Customers E-Loyalty Towards Imported Cosmetics Brands Through Customers E-Satisfaction - Retno Tri Handayani; Annie Susanto (International Journal of Social Science and Business, 2020)
In this era, globalization as well as the emergence of technology has led to online shopping trend especially among Generation Z who could not be separated from technology. This trend has also created an open market for countries to distribute their products. In any online businesses, e-loyalty and e-trust have been some of the important issues that might create obstacles on having long-term profits because lack of/low customer loyalty. Therefore, this study aimed at analysing and finding the influence of E-Trust, User’s Experiences, and Brand Equity on Gen Z female Customers’ E-Loyalty towards imported cosmetics brands through Customers’ E-Satisfaction. The population of this study was Gen Z female community in Indonesia with the samples of 200 respondents taken by non-probability sampling technique. The qualitative method used in this study was supported by the data collection through questionnaires spread in three areas; Central Java, West Java and outside Java. The data analysis method used was multiple linear regression analysis. The result showed that E-Trust in this study did not have a positive effect on Customers’ E-satisfaction while User’s Experiences and Brand Equity had positive effects on Customers’ E-Satisfaction. Other than that, Customers’ E-Satisfactions did not mediate the influence of E-Trust, User’s Experiences and Brand Equity on Customers’ Loyalty.